2021
DOI: 10.17509/jsl.v4i3.30366
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Preservice Science Teachers’ Cognitive Structures on Environmental Issues

Abstract: Environmental knowledge and awareness of individuals affect their attitudes and behavior toward the environment. In this regard, it is essential to specify how environmental issues are interpreted in individuals’ cognitive structures. This study aims to investigate preservice science teachers’ cognitive structures on environmental issues. The study was conducted with 78 third-year preservice science teachers. The data were collected through a word association test that contains eight stimulus words about envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Environmental knowledge and awareness influence an individual's attitudes and behaviour toward the environment (Kiryak et al, 2021). Environmental literacy is not only the responsibility of science teachers; future teachers from other academic disciplines must also be equipped with this competence.…”
Section: Resultsmentioning
confidence: 99%
“…Environmental knowledge and awareness influence an individual's attitudes and behaviour toward the environment (Kiryak et al, 2021). Environmental literacy is not only the responsibility of science teachers; future teachers from other academic disciplines must also be equipped with this competence.…”
Section: Resultsmentioning
confidence: 99%
“…Various kinds of literature related to environmental problems including pollution problems were found in several studies. Generally, research is conducted on pre-service teachers, elementary school students, and secondary schools (Celikler & Aksan, 2011;Özsoy & Ahi, 2014;Cetin, 2015;Pinar & Yakisan, 2017;Demirel & Kiroğlu, 2021;Kiryak et al, 2021;). Research from Pınar & Yakışan (2017) tried to find out elementary school students' perceptions of the environment by analyzing students' drawings about the environment and the results showed that most students described that environmental pollution is caused by garbage.…”
Section: Introductionmentioning
confidence: 99%
“…The OECD (2022) presented that <1 in five 15-year-olds in OECD countries could explain environmental phenomena in the PISA 2006, and students' scientific knowledge strongly correlated with understanding environmental issues. Moreover, numerous studies indicate that students worldwide with limited environmental knowledge and skills also have misconceptions about environmental issues (Kiryak et al, 2021;Palmer et al,1996;Spiteri, 2021;Wyner and Blatt, 2019), including bioaccumulation and biomagnification (Kim and Kim, 2013).…”
Section: Introductionmentioning
confidence: 99%